Hard lesson from a lost island - Abd Razak, Dzulkifli (2008)
IT may be accurate to describe the recent International Court of Justice decision on the disputed "rock islands" between Malaysia and its southern neighbour as a "winwin" situation. On the surface that is what it appears to be, although some would argue that the "winwin" is not necessarily in equivalent terms. But that is for them to argue it out. What is sad of course is that another part of peninsular Malaysia is now no longer with us. The historical fact remains that Pulau Batu Putih used to be an integral part of the Johor sultanate as documented in the ICJ submission.